The Relationship Between Parent's Education and Performance on Math and Reading Tests - Bell, Marilee; Starkey, John D. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
One hundred six freshman students were studied as to their performance on mathematics and reading tests in relation to their parents' education. These tests were local tests and were not based on national norms. Results showed that the mother's education influenced the test performance more than the father's, but both mother's and father's education tended to show relationship between mathematics and reading performance. The relationship between student scores on the reading and the mathematics tests also showed up substantially. (Author/DT)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Achievement; Mathematics; Mathematics Education; Parent Education; Reading Achievement; Research; Reports, Research